Analisa Kekakuan Pelat Galvanil Ketebalan 0,6 mm Terhadap Pembentukan Bead Roll dengan Variasi Ukuran dan Bentuk Trapesium - Harsono, Abimanyu; Erwanto, Erwanto; Ariyanto, Ariyanto (Manutech : Jurnal Teknologi Manufaktur, 2024)
Thin plates are a common material used in the automotive industry for vehicle panels. Galvanized metal materials are typically selected for use in vehicle panel construction due to their ductile nature, malleability, and resistance to corrosion. The function of vehicle panels is of great consequence with regard to the safety and comfort of the vehicle. The level of comfort experienced by vehicle occupants is influenced by noise, which is a consequence of vibrations generated by the engine and the road surface. The detrimental effects of excessive vibration can be mitigated by enhancing the rigidity of the panel. One method of achieving this is through the formation of a groove profile on the panel's surface, utilizing a bead roll process. The objective of this study is to ascertain the impact of variations in the width and depth of the groove, with a trapezoidal shape, on the stiffness of 0.6 mm thick galvanized plates for natural frequency response. The research method entailed the creation of an experimental design, the formation of a groove profile through the bead roll process, and the subsequent natural frequency testing of the plates using a Vibroport 80. The results of this testing were then subjected to analysis. The findings indicated that the variation in groove width and depth had no discernible impact on the plate stiffness with respect to the natural frequency response.